Workshop “Modern problems of Soft Matter Theory” - Barthel, J.; Mryglod, I. (Condensed Matter Physics, 2001)
The two subsequent issues of the journal “Condensed Matter Physics” contain the papers submitted to the Workshop “Modern problems of Soft Matter Theory”1 .